Case Report: Deficiency of Adenosine Deaminase 2 Presenting With Overlapping Features of Autoimmune Lymphoproliferative Syndrome and Bone Marrow Failure - Dell’Orso, Gianluca; Grossi, Alice; Penco, Federica; Caorsi, Roberta; Palmisani, Elena; Terranova, Paola; Schena, Francesca; Lupia, Michela; Ricci, Erica; Montalto, Shana; Pierri, Filomena; Ceccherini, Isabella; et al. (Frontiers in Immunology, 2021)
Deficiency of adenosine deaminase 2 (DADA2) is an autosomal recessive disease associated with a highly variable clinical presentation, such as vasculitis, inflammation, and hematologic manifestations. Some associations of clinical features can mimic autoimmune lymphoproliferative syndrome (ALPS). We report a case of a female patient who fulfilled the 2009 National Institute of Health revised criteria for ALPS and received a delayed diagnosis of DADA2. During her childhood, she suffered from autoimmune hemolytic anemia, immune thrombocytopenia, and chronic lymphoproliferation, which partially responded to multiple lines of treatments and were followed, at 25 years of age, by pulmonary embolism, septic shock, and bone marrow failure with myelodysplastic evolution. The patient died from the progression of pulmonary disease and multiorgan failure. Two previously unreported variants of gene ADA2/CECR1 were found through next-generation sequencing analysis, and a pathogenic role was demonstrated through a functional study. A single somatic STAT3 mutation was also found. Clinical phenotypes encompassing immune dysregulation and marrow failure should be evaluated at the early stage of diagnostic work-up with an extended molecular evaluation. A correct genetic diagnosis may lead to a precision medicine approach consisting of the use of targeted treatments or early hematopoietic stem cell transplantation.